Effect of elevated tropospheric ozone on soil carbon and nitrogen: a meta-analysis. (1st April 2022) - Hu, Enzhu; Ren, Zhimin; Wang, Xiaoke; Zhang, Hongxing; Zhang, Weiwei
Abstract: Elevated tropospheric ozone concentration ([O3 ]) may substantially influence the belowground processes of the terrestrial ecosystem. Nevertheless, a comprehensive and quantitative understanding of the responses of soil C and N dynamics to elevated [O3 ] remains elusive. In this study, the results of 41 peer-reviewed studies were synthesized using meta-analytic techniques, to quantify the impact of O3 on ten variables associated with soil C and N, i.e. total C (TC, including soil organic C), total N (TN), dissolved organic C (DOC), ammonia N (NH4 + ), nitrate N (NO3 − ), microbial biomass C (MBC) and N (MBN), rates of nitrification (NTF) and denitrification (DNF), as well as C/N ratio. The results depicted that all these variables showed significant changes ( P < 0.05) with [O3 ] increased by 27.6 ± 18.7 nl l −1 (mean ± SD), including decreases in TC, DOC, TN, NH4 +, MBC, MBN and NTF, and increases in C/N, NO3 − and DNF. The effect sizes of TN, NTF, and DNF were significantly correlated with O3 fumigation levels and experimental duration ( P < 0.05). Soil pH and climate were essential in analyses of O3 impacts on soil C and N. However, the responses of most variables to elevated [O3 ] were generally independent of the O3 fumigation method, terrestrial ecosystem type, and additional [CO2 ] exposure. The altered soil C and N dynamics under elevated [O3 ] may reduce its C sink capacity, and change soil N availability and thus, impact plant growth and enhance soil N losses.